Losartan Alleviates Renal Fibrosis and Inhibits Endothelial-to-Mesenchymal Transition (EMT) Under High-Fat Diet-Induced Hyperglycemia - Yao, Yufeng; Li, Yong; Zeng, Xiaofei; Ye, Zheng; Li, Xia; Zhang, Lu (Frontiers in Pharmacology, 2018)
The endothelial-to-mesenchymal transition (EMT) of glomerular vascular endothelial cells is considered to be pivotal in diabetic nephropathy (DN). The risk of DN can be decreased by losartan, but the potential molecular mechanism(s) are not fully understood. Extensive data show that the EMT occurs in proximal tubular endothelial cells resulting in an endothelial phenotype switch (fibrotic matrix accumulation), consequently enhancing the development of renal interstitial fibrosis. Here, we found that losartan significantly ameliorated DN-induced renal fibrosis progression via inhibition of the EMT in mice. In vivo experiments suggested that losartan significantly alleviated microalbuminuria and pathologic changes under high-fat diet-induced hyperglycemia stress. Immunohistochemistry indicated that losartan suppressed the EMT in glomeruli. In addition, losartan decreased oxidative stress damage and inhibited the transforming growth factor (TGF)-β1/Smad pathway. Furthermore, consistent changes were detected in vitro where losartan markedly inhibited the EMT and TGF-β1/Smad pathway induced by high glucose in glomerular endothelial cells. Together, these results suggested that losartan could alleviate the EMT in glomeruli via inhibition of oxidative stress damage and the TGF-β1/Smad signaling pathway under hyperglycemia stress.